2014
DOI: 10.1002/2013jd020566
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric ozone response to sulfate geoengineering: Results from the Geoengineering Model Intercomparison Project (GeoMIP)

Abstract: Geoengineering with stratospheric sulfate aerosols has been proposed as a means of temporarily cooling the planet, alleviating some of the side effects of anthropogenic CO 2 emissions. However, one of the known side effects of stratospheric injections of sulfate aerosols under present-day conditions is a general decrease in ozone concentrations. Here we present the results from two general circulation models and two coupled chemistry-climate models within the experiments G3 and G4 of the Geoengineering Model I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
253
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(274 citation statements)
references
References 117 publications
14
253
0
Order By: Relevance
“…The explicitly calculated effective radius (ULAQ-CCM) or indirectly derived 15 using the Grainger et al (1995) method (GEOS-Chem) are both consistent with the SAGE-II derived estimates approximately one year after the Pinatubo eruption, with comparable integrated stratospheric sulfate mass (Pitari et al (2014); Visioni et al (2017b)). The breakdown of global SO x deposition fluxes, among SO 2 , SO 4 dry and wet deposition terms, is summarized in Table 4 for the two models, and a comparison is made with multimodel data presented in Lamarque et al (2013).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The explicitly calculated effective radius (ULAQ-CCM) or indirectly derived 15 using the Grainger et al (1995) method (GEOS-Chem) are both consistent with the SAGE-II derived estimates approximately one year after the Pinatubo eruption, with comparable integrated stratospheric sulfate mass (Pitari et al (2014); Visioni et al (2017b)). The breakdown of global SO x deposition fluxes, among SO 2 , SO 4 dry and wet deposition terms, is summarized in Table 4 for the two models, and a comparison is made with multimodel data presented in Lamarque et al (2013).…”
supporting
confidence: 65%
“…Important model updates regarding horizontal and vertical resolution (now T21 with 126 log pressure levels), species cross sections and Schumann-Runge bands treatment, and upgrades of the radiative transfer code were described and tested in Pitari et al (2014). This radiative module, crucial for a good prediction of the sulfate aerosol interaction 10 with shortwave solar and longwave planetary radiation has been tested for tropospheric aerosols in SPARC-AEROCOM (Randles et al (2013)) and also for stratospheric aerosols after major volcanic eruptions (Pitari et al (2016b)).…”
Section: Ulaq-ccmmentioning
confidence: 99%
“…Early modeling research in geoengineering showed that solar geoengineering schemes could markedly diminish regional and seasonal climate change caused by increase in CO 2 concentration (Govindasamy and Caldeira 2000;Govindasamy et al 2003). In the recent past, several modeling studies have investigated solar geoengineering using stratospheric sulfate aerosols (Robock et al 2008;Modak and Bala 2014;Tilmes et al 2009;Pitari et al 2014;Niemeier and Timmreck 2015). Other geoengineering methods such as marine cloud brightening and ocean albedo modification are also discussed in detail in several reviews (Bala 2009;Lenton and Vaughn 2009;Caldeira et al 2013;NRC Report 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfuric acid, H 2 SO 4 , can accelerate ozone loss by forming aqueous aerosol that catalyzes reactions such as HCl + ClONO 2 → Cl 2 + HNO 3 , shifting halogens from reservoir species to reactive compounds and altering the NO x budget via hydrolysis of N 2 O 5 to HNO 3 . Previous studies found that injection of sufficient SO 2 or particulate sulfate to produce −2 W·m −2 of radiative forcing-a useful benchmark for SRM-reduced average column ozone by 1 to 13% (2,(6)(7)(8).…”
mentioning
confidence: 99%